PENYULUHAN HUKUM PENGGUNAAN INTERNET DAN IMPLIKASINYA BAGI PELAJAR DI SMA NEGERI 1 MEDAN DAN SMK NEGERI 8 MEDAN - Eko Yudhistira; Syarifah Lisa; Faradila Sitepu (Talenta Publisher, 2019)
This society service activity is purposed to give an elucidation of law about the usage of internet which is growing massively in society especially in the students social environment. The improvement of internet usage caused higher risk of crime in the society. government gives the limitation in the usage of internet by issued UU No.19/2016 about the change of UU No.11 Tahun 2008 (Act Number 19 of the year 2016 about the change of Act Number 11 of the year 2008) about information and electronic transaction. As legal state, the persumptio iures de iure norm or mostly called as law fiction is the logic consequence of legal state. Law fiction means that the state assume everyone know the law, not limiting the citizen who live in the rural or even the one who still studying at school like students. The rules about the usage of internet like hoax, porn, hate speech, slander, or good name vilification and other form which can caused a law consequence by like, repost, re-tweet, share, post, auto tag or etc. this is the responsibility of government by the existence of university to socialize the law therefore the society especially the students become more wise in using the internet.